RELEVANSI LABORATORIUM HUKUM DALAM MENINGKATKAN KOMPETENSI MAHASISWA - Lubis, Risyad Fakar; Budhiawan, Adlin (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2024)
The law laboratory is an essential facility that provides students with practical experience in applying the legal theories learned in class. The aim of this research is to assess the extent to which the law laboratory contributes to the development of practical skills, such as case analysis, legal communication, and argumentative abilities, as well as non-technical skills, such as teamwork and conflict management. The research methodology employs a descriptive qualitative approach, with data collection conducted through in-depth interviews, observations, and focus group discussions (FGDs) involving students, lecturers, and legal practitioners. The findings indicate that the law laboratory plays a significant role in improving both the technical and non-technical skills of students. Those actively participating in laboratory activities, such as trial simulations and negotiation exercises, demonstrate substantial improvements in their understanding of procedural law and their preparedness for entering the professional world. The research also highlights several challenges, including limited laboratory facilities and resources, as well as the need for an increase in the number of lecturers with practical legal experience. Recommendations from this study include enhancing laboratory facilities, integrating the law laboratory more structurally into the curriculum, and developing external collaborations with legal institutions to provide students with a more diverse range of experiences. Thus, it is hoped that the law laboratory can serve as a more effective instrument in producing law graduates who are competent and ready to compete in the global job market